SISTEM TELEMEDICINE BERBASIS AGILE UNTUK MENINGKATKAN AKSES KESEHATAN DAERAH TERPENCIL - Maria Lusiana Vebronia Mazok; Surtikanti Surtikanti (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
Limited access to healthcare services remains a major challenge in remote areas due to geographical barriers, limited medical personnel, and inadequate infrastructure. This study focuses on the development of a telemedicine information system aimed at improving access to healthcare services in remote regions. The system was developed using the Agile method, which allows flexible and iterative development through planning, design, implementation, and testing stages. The developed system provides essential features such as remote medical consultation and patient data management. The results indicate that the telemedicine system can support more efficient healthcare service delivery and facilitate access to medical services for communities in remote areas.